The correlation between English learning anxiety and students’ speaking performance - Weni Ratnasari; Rizky Yolanda; Zelly Putriani (Journal of Research in English Language Teaching and Linguistics, 2025)
The interplay between anxiety and speaking performance in English as a Foreign Language (EFL) learners is a critical area of investigation, given its implications for language acquisition and instructional strategies. Anxiety, particularly in oral communication, has been identified as a major psychological barrier that hampers learners’ confidence, fluency, and participation, thereby affecting both immediate performance and long-term language development. Although existing research underscores the negative impact of language anxiety, there is a notable gap in empirical studies that directly correlate anxiety levels with standardized speaking performance scores within classroom settings, especially among non-native English learners. This study aims to examine the relationship between English learning anxiety and students’ speaking proficiency, utilizing validated anxiety scales and performance assessments to quantify this connection. Employing a correlational research design, the study involved 48 undergraduate students enrolled in an English language program at an Indonesian university, divided into high- and low-anxiety groups based on their scores on the Foreign Language Classroom Anxiety Scale (FLCAS). Data collection involved administering the FLCAS and evaluating speaking performance through a standardized rubric aligned with the Common European Framework of Reference (CEFR). The collected data were analyzed using statistical methods to determine the strength and direction of the relationship between anxiety levels and speaking scores. Key findings reveal a significant inverse correlation: students with higher anxiety levels consistently demonstrated lower speaking performance, while those with lower anxiety performed better. These results underscore the detrimental role of anxiety in oral language production and suggest that reducing affective barriers can enhance learners’ speaking proficiency. The study implies that language educators should incorporate anxiety-reduction strategies into their pedagogy, fostering supportive environments that encourage participation and boost confidence, ultimately improving language acquisition outcomes.